Sosialisasi Inovasi Tata Kelola Digital: (E- Government/Smart Governance) di SMK PGRI 4 Kota Serang - Saidsy, Abdul Mutholib; Rofah, Rofah; Nabilah, Afiyah; Maryani, Lala Tri; Wahyudi, Heru (AMERTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACT Digital transformation in educational governance is a strategic step to enhance transparency, efficiency, and school community participation. The concept of Smart Governance, rooted in collaboration and information technology integration, can be adapted within schools to strengthen administrative systems and decision-making processes. This Community Service (PkM) activity was conducted at SMK PGRI 4 Kota Serang with the aim of providing education on the concept and implementation of E- Government/Smart Governance in school governance. The methods included material presentation, interactive discussions, digital governance simulations, the use of visual media, and evaluation through questionnaires. The results indicated an increased understanding among students regarding digital governance concepts, more active participation in discussions, and greater awareness of the importance of digital infrastructure in supporting academic and administrative services This activity is expected to contribute to expanding the study of E-Government/Smart Governance in the education sector while strengthening digital governance practices in vocational schools, thereby supporting the creation of a more adaptive, transparent, and participatory management system. Keywords: digital governance, e-government, smart governance, community service. ABSTRAK Transformasi digital dalam tata kelola pendidikan merupakan langkah strategis untuk meningkatkan transparansi, efisiensi, dan partisipasi warga sekolah. Konsep Smart Governance yang berakar pada prinsip kolaborasi dan integrasi teknologi informasi dapat diadaptasi dalam lingkungan sekolah untuk memperkuat sistem administrasi dan pengambilan keputusan. Kegiatan Pengabdian kepada Masyarakat (PkM) ini dilaksanakan di SMK PGRI 4 Kota Serang dengan tujuan memberikan edukasi mengenai konsep dan penerapan E-Government/Smart Governance dalam tata kelola sekolah. Metode kegiatan meliputi presentasi materi, diskusi interaktif, simulasi tata kelola digital, penggunaan media visual, serta evaluasi melalui kuesioner. Hasil kegiatan menunjukkan adanya peningkatan pemahaman siswa terhadap konsep tata kelola digital, partisipasi diskusi yang lebih aktif, serta kesadaran akan pentingnya infrastruktur digital dalam mendukung layanan akademik dan administrasi. Kegiatan ini diharapkan dapat memberikan kontribusi dalam memperluas kajian E- Government/Smart Governance di sektor pendidikan sekaligus memperkuat praktik tata kelola digital di sekolah kejuruan, sehingga mendukung terciptanya sistem manajemen yang lebih adaptif, transparan, dan partisipatif. Kata kunci: tata kelola digital, e-government, smart governance, pengabdian kepada masyarakat.